Continuous-Flow Kinetic Resolution of (±)-cis-1-Amino-2-indanol by Lipase-Catalyzed N-Acetylation - Kim, Yoon-Jung; Choi, Yong-Sung; Yang, Sai; Yang, Woo Ram; Jeong, Jin-Hyun (Synlett, 2015)
Selective N-acetylation of (1S,2R)-1-amino-2-indanol by immobilized lipase B from Candida antarctica showed high enantiomeric excess when ethyl acetate was used as the acyl donor in a THF solution. Combining this process with continuous-flow system, we could obtain enantiomerically pure N-acetyl-aminoindanol at a flow rate of 0.1 mL/min (residence time of 64 min). It has been demonstrated to be more efficient compared to the flask mode.
Keywords: (±)-cis-1-amino-2-indanol; Novozyme 435®; continuous-flow system; kinetic resolution; selective N-acetylation